The role of virus infections in Sjögren’s syndrome - Maslinska, Maria; Kostyra-Grabczak, Kinga (Frontiers in Immunology, 2022)
Abstract The primary Sjogren’s syndrome (pSS) is an autoimmune disease with a clinical picture of mainly exocrine gland involvement, with dryness symptoms, but also with internal organ and systems involvement. The epithelial damage and releasing of antigens, which in some circumstances become autoantigens, underlay the pathogenesis of pSS. The activation of autoimmune processes in pSS leads to the hyperactivation of B cells with autoantibodies production and other immunological phenomena, such as hypergammaglobulinemia, production of cryoglobulins or formation of extra-nodal lymphoid tissue. Among the risk factors for the development of this disease are viral infections, which themselves can activate autoimmune reactions and influence the host's immune response. It is known, that viruses through various mechanisms can influence the immune system and initiate autoimmune reactions. These mechanisms include a molecular mimicry, bystander activation, production of superantigens – proteins encoded by viruses - or a programming to produce viral cytokines similar to host cytokines, such as e.g. Interleukin-10. Of particular importance for pSS are viruses, which not only, as expected, activate the interferon pathway, but also play a particular role, directly or indirectly, in B cells activation or present tropism to organs also targeted in the course of pSS. This article is an attempt to present the current knowledge of the influence specific viruses have on the development and course of pSS.